Implementation of Edpuzzle to Improve Students’ Analytical Thinking Skill in Narrative Text - Amaliah, Amaliah (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2020)
Digital learning has become one of the demands of life to prepare students to become part of global society 5.0. as cultured human being. For this reason, it is very important that students learn to be creative, collaborative, communicative, and able to think critically. However, to achieve those all, the teacher really has to work hard in designing 4C learning. The purpose of this research is to describe the implementation of Edpuzzle to improve the students’analytical thinking skill in Narrative text at SMPN 2 Sidoarjo in the academic year 2018/2019 by using Edpuzzle in the even semester. The method used in this research is case study. It develops a detail background, case, investigation to solve a problem. The results obtained are: (1) The use of Edpuzzle can improve students’ analytical thinking skill, especially in Narrative text at SMPN 2 Sidoarjo (2) The use of Edpuzzle in the classroom is conducted and implemented with PISA method (Preliminarily, Intensive learning, Self-study and Assessment). This application is specifically used to overcome students' understanding and analytical thinking skills at a higher level. Students also increase their creativity in creating writing content that educates and promotes the Indonesian stories to the international languages.